Environmental Consciousness and Purchase Intention for Sustainable Eco-Friendly Pants: Evidence from Business Students in a Non-Sectarian University - Alysa S. Acoba; Elliane Jhane F. Siyang; Angelica Jorose V. Abing; Jolan P. Ancog; Jayvie O. Guballo (The Indonesian Institute of Science and Technology Research, 2026)
This study explores how environmental consciousness influences the purchase intention of sustainable eco-friendly pants among Marketing Management students at the National University–Manila. To determine the relationship between environmental consciousness and purchase intention, focusing on how knowledge, concern, values, attitudes, and perceived consumer effectiveness affect students’ decisions to buy sustainable apparel. The study employed a quantitative-descriptive and correlational research design using a structured questionnaire. A total of 267 Marketing Management students from the National University–Manila participated. Data were analyzed using frequency, percentage, weighted mean, Pearson Chi-Square, and Pearson correlation. Findings revealed that students have a high level of environmental consciousness and strong purchase intention toward eco-friendly pants. A significant positive relationship exists between environmental consciousness and purchase intention. Students with greater environmental awareness are more inclined to purchase sustainable products, confirming that environmental consciousness directly influences green consumer behavior. Educational institutions, businesses, and policymakers may develop sustainability programs, green marketing strategies, and fashion campaigns to encourage eco-friendly consumer practices among students.